Nanoscopic Al(1-x)Ce(x) phases in the NaH + Al + 0.02CeCl(3) system - Pitt, Mark; Paskevicius, Mark; Webb, C.; Sorby, M.; Delleda, S.; Jensen, T.; Hauback, B.; Buckley, Craig; Gray, E. (Elsevier Ltd, 2011)
The NaH + Al + 0.02CeCl3 system has been studied by high-resolution X-ray synchrotron diffraction and transmission electron microscopy (TEM), after planetary milling under hydrogen and hydrogen (H) cycling. Isothermal absorption kinetics were determined at 150 °C, and compared with the NaH + Al + 0.02TiCl3 system, indicating that CeCl3 and TiCl3 are equally effective additives, with CeCl3 preferred on the basis of hydrogen storage capacity. After milling, AlCe contains 100% of the Ce. After the first H absorption, we observe two Al1-xCex phases. The first, AlCe, contains ca. 60% of the originally added Ce atoms. The AlCe phase observed after milling and H cycling is chemically disordered, with complete exchange between the Al and Ce sublattices occurring, yielding zero intensity in ordering reflections such as (100). In the absorbed state after H cycling, the remaining 40% of Ce atoms are contained in a cubic Al1-xCex phase not previously observed in the Al-Ce phase diagram. Indexing yields a primitive cubic unit cell of dimension 7.7111 A°, in space group P23. Lineshape analysis indicates the AlCe and unknown cubic Al1-xCex phases are ca. 35 nm and 30 nm in dimension respectively. High resolution TEM imaging confirms that both Al1-xCex phases are embedded on the NaAlH4 surface, and localised energy dispersive X-ray spectroscopy (EDS) indicates a ca. 2:1 Al:Ce ratio for the unknown cubic Al1-xCex phase.